Code-Switching and Code-Mixing Phenomena in the IELTS Republic WhatsApp Group - Rostina Rostina; Dien Afni Ariyati; Sri Hariati Mustari; Ridwan Andi Mattoliang (Jurnal Pendidikan dan Sastra Inggris, 2025)
Code-switching and code-mixing are widespread linguistic practices that naturally occur in bilingual and multilingual communities. Within sociolinguistics, these phenomena are not only observed in direct face-to-face communication but also increasingly in online interactions, particularly on informal digital platforms such as WhatsApp. This study focuses on the IELTS Republic WhatsApp group, which consists of job seekers, scholarship applicants, and individuals preparing for the IELTS examination. The main objective of this research is to analyze and explore the kinds and contexts of code-switching and code-mixing employed by group members in their daily online interactions. The researchers adopted a qualitative descriptive design by applying a digital ethnography approach. Data were collected from group conversations that took place between 2023 and 2025. The discourse analysis method was then used to examine instances of code-switching and code-mixing, with a specific focus on identifying their forms and categorizing their functions. The analysis revealed that all three types of code-switching—intra-sentential, inter-sentential, and tag-switching—appeared with relatively equal dominance, alongside frequent occurrences of code-mixing. These practices were not random but rather motivated by pragmatic, cognitive, and social purposes. Pragmatically, code alternation facilitated clarity, emphasis, and effective communication. Cognitively, it reflected speakers’ ease in accessing multiple linguistic repertoires. Socially, it allowed members to demonstrate solidarity, express identity, and construct group belonging. The findings highlight that code-switching and code-mixing in digital communities function as important linguistic strategies that enable multilingual speakers to navigate complex communicative needs while negotiating identity in an online environment. This study contributes to a deeper understanding of language practices in digital ethnography and provides valuable insights for further research on multilingual communication in virtual spaces, especially in contexts where English functions as a global lingua franca.